Impacto de la estrategia de marketing digital en el posicionamiento de la marca Capieli en el mercado peruano en el contexto post pandemia Covid-19 - Valdivia Luna, Carol Melissa (2021)
This research aims to determine whether a digital marketing strategy that involves various digital media can increase the growth and improve the positioning of a new brand of clothing for babies and children, Capieli, in the post-covid-19 pandemic context, faster and more efficient than traditional marketing. With the information collected from secondary sources and from surveys carried out, it has been possible to conclude that the hypothesis raised is true, since for some years consumption through virtual media has been increasing, but thanks to the covid-19 pandemic this growth has risen. For this reason, the most effective form of growth for Capieli in this context is through digital media, which allow increasing its sales in the current market, which is mainly Lima, but also gives it the opportunity to expand its market, reaching provinces and other countries, using less economic resources but being more efficient. The main recommendations for the Capieli brand are: implement a digital marketing strategy that covers various digital media, such as social networks, email marketing and virtual store, to achieve greater growth in sales; and develop a good content plan for all media, since the best way to interact and connect emotionally with the virtual community is by delivering valuable content, and thus will achieve audience loyalty. Finally, it should be noted that with the research carried out, valuable information has been collected that can help other enterprises in the children's field to better know their target audience and know how to direct their efforts in digital marketing, in the same way other enterprises can take this research as a reference and adapt it to their needs.